2015
DOI: 10.1016/j.str.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

A Hinge Migration Mechanism Unlocks the Evolution of Green-to-Red Photoconversion in GFP-like Proteins

Abstract: Summary In proteins, functional divergence involves mutations that modify structure and dynamics. Here, we provide experimental evidence for an evolutionary mechanism driven solely by long-range dynamic motions without significant backbone adjustments, catalytic group rearrangements, or changes in subunit assembly. Crystallographic structures were determined for several reconstructed ancestral proteins belonging to a GFP class frequently employed in superresolution microscopy. Their chain flexibility was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
173
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(192 citation statements)
references
References 54 publications
18
173
0
1
Order By: Relevance
“…As compared to the green-state structure obtained from a non-illuminated crystal, the red-state structure of IrisFP reveals cleavage of the peptide bond between the amide nitrogen and the α-carbon of His62, the first amino acid of the chromophore. Similar structural changes associated with green-to-red photoconversion have been observed in all PCFPs investigated by crystallography thus far, including Dendra2 [32], Kaede [33], KikGR [34], pcDronpa [16] and a least-evolved ancestral PCFP [35]. A double bond on the His62 side chain is formed, leading to extension of the chromophore conjugated π-system and the associated red shift.…”
Section: Green To Red Photoconversionmentioning
confidence: 54%
“…As compared to the green-state structure obtained from a non-illuminated crystal, the red-state structure of IrisFP reveals cleavage of the peptide bond between the amide nitrogen and the α-carbon of His62, the first amino acid of the chromophore. Similar structural changes associated with green-to-red photoconversion have been observed in all PCFPs investigated by crystallography thus far, including Dendra2 [32], Kaede [33], KikGR [34], pcDronpa [16] and a least-evolved ancestral PCFP [35]. A double bond on the His62 side chain is formed, leading to extension of the chromophore conjugated π-system and the associated red shift.…”
Section: Green To Red Photoconversionmentioning
confidence: 54%
“…However, protein structure-encoded conformational dynamics, which span a broad timescale of motion from atomic fluctuations and side chain rotations to collective domain movements, underlie a protein’s biological function. Protein evolution studies of several different protein families have shown that changes in conformational dynamics through allosteric regulation lead to new functions(e.g., green fluorescent protein (GFP), beta-lactamase inhibitors, and nuclear receptors [5254]). Moreover evolutionary rates are strongly correlated with the flexibility of individual positions obtained from conformational dynamics [5557].…”
Section: Conformational Dynamics and Allostery In Disease Developmentmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations and PRS of reconstructed ancestral proteins of green fluorescent protein (GFP) shows the evolution of red color from a green ancestor emerged by migration of the hinge point from the active site diagonally across the beta-barrel fold (44). Although the flexibility of the mutational sites does not change in allosteric response to these mutants, both an increase in flexibility (softening) and decrease in flexibility (hardening) occurs for the regions of the beta fold that are widely separated.…”
Section: Introductionmentioning
confidence: 99%